Financial Performance and CSR as Determinants of Auditors' Going Concern Judgments: Evidence from Indonesian Infrastructure State-Owned Enterprises - Rengga Anisa Arpi Mevia; Lenda Komala; Andri Gunawan (Research of Accounting and Governance, 2026)
This study examines the effects of financial performance and Corporate Social Responsibility (CSR) on auditors' going concern opinions among Indonesian infrastructure State-Owned Enterprises (SOEs) during the 2019–2024 period. Financial performance is measured using the Current Ratio (CR), Return on Assets (ROA), and Debt-to-Asset Ratio (DAR). In contrast, CSR is measured using the Corporate Social Responsibility Disclosure Index (CSRDI) based on annual report disclosures. The dependent variable is coded as 1 for firms receiving a going concern opinion and 0 otherwise. Using a quantitative approach, this study analyzes 54 firm-year observations from nine infrastructure SOEs through logistic regression. The findings indicate that profitability, leverage, and CSR significantly influence auditors' going concern opinions, whereas liquidity does not have a significant effect. These results suggest that auditors consider both financial and non-financial information when assessing a company's ability to maintain business continuity. This study contributes to the literature by integrating financial performance and CSR within a single analytical framework and providing updated evidence from Indonesian infrastructure SOEs during the pandemic and post-pandemic periods, a research context that has received limited empirical attention.